The one China principle and its legal consequences, domestically and abroad: the disputed control over Taiwan and the anti-secession law. Much Ado about Nothing? (TEST Trento Student Law Review, 2022)
The article explores two of the fundamental characteristics of the one China principle: from an international perspective, and from a domestic one. The first paragraph, which analyses international law relevant to the matter, deals with the disputed sovereignty of the Republic of China, commonly named Taiwan. The second one explores the hidden meaning and the preparatory works of a domestic Chinese (People's Republic of China) statute: the anti-secession law. Because of this contested sovereignty, it is debated if people in Taiwan would be protected by the UN Charter in case of armed aggression. The first part of these pages will be consequently dedicated to demonstrating how the island of Formosa falls under UN jurisdiction and specifically that Taiwan meets all the criteria for statehood. As for the second chapter, it will be argued that the anti-secession law, despite an aggressive attitude, did not increase the chances for armed aggression against the Republic of China, as it was passed to appease the increasing nationalist public opinion.
Keywords: Law; China; Taiwan; Sovereignty; Anti-secession